The effectiveness of pre-reading activity by using QARS towards students reading comprehension at A2 level - Afifah, Alif Jihan; Yuniar, Rendhi Fatrisna (Journal of English Language Teaching and Learning (JETLE), 2024)
Reading is a receptive skill that involves decoding the written symbol and understanding the meaning. According to CEFR Framework the reading abilities are divided into several level namely: A1, A2, B1, B2, C1, and C2. Throughout the level the educator can adapt the material for student capability. The study object determine the effectiveness pre-reading activity using the question-answer strategy (QARS) to improve the reading comprehension a A2 level. The study employed the quantitative method, involving 57 students in eleventh-grade from MAN 1 MALANG, by divided into experimental and control groups. The data collected using pre-test and post-test by analyzed Mann-Whitney U test which obtained the P-values 0.00. The result revealed that the experimental group achieved a significantly higher score 89.25 which compared to control class who achieved score76.66. These study finding suggest the incorporation QARS into Pre-reading activities to enhance students reading comprehension. The study implication engage the educator to integrate the QARS into their teaching strategies to foster the critical thinking for student.